2011
DOI: 10.1007/s10705-011-9429-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of intensively grazed ryegrass dairy pastures to fertiliser phosphorus and potassium

Abstract: Intensively grazed, rain-fed dairy pastures on the predominantly sandy soils in the high rainfall ([800 mm annual average) Mediterranean-type climate of south-western Australia comprise [90% ryegrass (annual ryegrass, Lolium rigidum Gaud. and Italian ryegrass, L. multiflorum Lam.). To maximise pasture use for milk production, the pastures are rotationally grazed by starting grazing when ryegrass plants have 3 leaves per tiller, and fertiliser nitrogen (N) and sulfur (S), in the ratio of 3-4 N and 1S, need to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The observed response of DM yield to P fertilisation of our experiment was more or less in line with results reported for multiple-year experiments in grazed grassland. Reported responses of DM yield range from 0 up to 110 kg DM kg -1 P (Bolland et al 2011;Bolland and Guthridge 2007;Davison et al 1997), responses of P yield were not mentioned.…”
Section: Herbage Response To P Fertilisationmentioning
confidence: 99%
“…The observed response of DM yield to P fertilisation of our experiment was more or less in line with results reported for multiple-year experiments in grazed grassland. Reported responses of DM yield range from 0 up to 110 kg DM kg -1 P (Bolland et al 2011;Bolland and Guthridge 2007;Davison et al 1997), responses of P yield were not mentioned.…”
Section: Herbage Response To P Fertilisationmentioning
confidence: 99%
“…Pasture‐based dairy production systems in Western Australia (WA) differ from most other dairy areas in Australasia due to the Mediterranean climate and sandy soil type in the region. The majority of farms operate a dryland production system where the typical rain‐fed pasture growing season lasts from approximately May to November, with negligible growth occurring in the warm, dry period between December and April (Bolland, Guthridge, & Blincow, ; McDonnell, Staines, Edmunds, & Morris, ). Due to these environmental conditions, dairy pastures have historically comprised a mix of annual ryegrass ( Lolium rigidum Gaud.)…”
Section: Introductionmentioning
confidence: 99%
“…and Italian ryegrass ( L. multiflorum Lam. ), together with subterranean clover ( Trifolium subterraneum L.), with these species completing their growth cycles and setting seed before the onset of moisture stress at the end of the growing season (Bolland et al., ; Callow, Michell, Baker, & Hough, ). Dairy production systems in the region have intensified significantly over the last two decades (Bolland & Guthridge, ), with use of N fertilizer becoming commonplace and farmers adopting the 3‐leaf grazing management principles outlined by Fulkerson and Donaghy ().…”
Section: Introductionmentioning
confidence: 99%
“…Data from experiments on permanent grassland, which is not grazed, generally show stable P-test values at P surpluses close to equilibrium (Schils & Snijders, 2004;Stroia et al, Changes in soil P pools at balanced fertilizer application 9 2007; Messiga et al, 2015), or even a slight increase in P-test values (Gallet et al, 2003;Malhi et al, 2003). On the other hand, data from permanent grazed grassland often show a decline in P-test values at P surpluses close to equilibrium (Condron & Goh, 1989;Davison et al, 1997;Bolland et al, 2011). Data from the grazed Winchmore long-term trial in New Zealand (Condron & Goh, 1989) showed a decline in both readily available and more residual bound inorganic P pools at a slight P deficit [zero P application in combination with small output of animal products (<1.4 kg P/ha)].…”
Section: Comparison With Data From Other Long-term Field Experimentsmentioning
confidence: 99%